2002
DOI: 10.1190/1.1527072
|View full text |Cite
|
Sign up to set email alerts
|

Biot–Gassmann theory for velocities of gas hydrate‐bearing sediments

Abstract: Elevated elastic velocities are a distinct physical property of gas hydrate‐bearing sediments. A number of velocity models and equations (e.g., pore‐filling model, cementation model, effective medium theories, weighted equations, and time‐average equations) have been used to describe this effect. In particular, the weighted equation and effective medium theory predict reasonably well the elastic properties of unconsolidated gas hydrate‐bearing sediments. A weakness of the weighted equation is its use of the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 20 publications
2
134
0
2
Order By: Relevance
“…Contrary to Gassmann's (1951) assumption, Lee (2002) showed that the shear modulus also exhibits a dependence on the rock's water saturation, w S , and proposed the following formula for the shear modulus of a fluid-saturated rock: 222 * 2…”
Section: B32 Relation Between Rock Physics and Petrophysical Promentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to Gassmann's (1951) assumption, Lee (2002) showed that the shear modulus also exhibits a dependence on the rock's water saturation, w S , and proposed the following formula for the shear modulus of a fluid-saturated rock: 222 * 2…”
Section: B32 Relation Between Rock Physics and Petrophysical Promentioning
confidence: 99%
“…In determining the relationship between elastic moduli with porosity and saturation we use Lee's (2002) extension of the Biot-Gassmann model. With the sensitivity study we observe that the sensitivity of porosity to the seismic velocities (both P-and S) is considerable while that of the saturation is insignificant.…”
Section: B36 Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exponent m is a function of porosity Φ (Goldberg and Gurevich 1998;Lee 2002). The parameter M can be obtained from the relation: , (2.11)…”
Section: Modified Biot-gassmann Modelmentioning
confidence: 99%
“…Two different approaches were used to relate the hydrate saturation and velocity in oceanic sediments: (1) empirical methods including Wyllie's time average [Wyllie et al, 1958;Pearson et al, 1983], Wood's equation [Wood, 1941] and weighted combinations of the Wyllie's time average and Wood's equation [Lee et al, 1996], and (2) physics-based models, such as the effective medium theory (EMT) [Helgerud et al, 1999;Dvorkin and Prasad, 1999] and the Biot-Gassmann theory modified by Lee (BGTL) [Lee, 2002a[Lee, , 2002b[Lee, , 2003]. However, the gas hydrate volumes within sediments estimated with these approaches are quite different.…”
Section: Introductionmentioning
confidence: 99%